Double-hit separation and dE/dx resolution of a time projection chamber with GEM readout. (1st November 2022) - Aoki, Y.; Attié, D.; Behnke, T.; Bellerive, A.; Bezshyyko, O.; Bhattacharya, D.S.; Bhattacharya, P.; Bhattacharya, S.; Chang, Y.; Colas, P.; De Lentdecker, G.; Dehmelt, K.; et al.
Abstract: A time projection chamber (TPC) with micropattern gaseous detector (MPGD) readout is investigated as main tracking device of the International Large Detector (ILD) concept at the planned International Linear Collider (ILC). A prototype TPC equipped with a triple gas electron multiplier (GEM) readout has been built and operated in an electron test beam. The TPC was placed in a 1 T solenoidal field at the DESY II Test Beam Facility, which provides an electron beam up to 6 GeV/ c . The performance of the readout modules, in particular the spatial point resolution, is determined and compared to earlier tests. New studies are presented with first results on the separation of close-by tracks and the capability of the system to measure the specific energy loss d E /d x . This is complemented by a simulation study on the optimization of the readout granularity to improve particle identification by d E /d x .